Dampak Strategi Bisnis terhadap Penghindaran Pajak - Sekar Akrom Faradiza (Journal of Applied Accounting and Taxation, 2019)
In carrying out business processes of a company, managers must make decisions related to business strategies. The strategy chosen by the company can be one of the typologies according to Miles & Snow namely the prospector, defender, analyzer and reactor. The strategy chosen by the company will affect all activities in the company including tax activities inherent in business activities so that any decisions made by managers have consequences on tax, one of which is tax avoidance. This study aims to examine the impact of the strategy on tax avoidance. This research used manufacturing company that has been listed on the Indonesia Stock Exchange from 2010 to 2016 and Independent sample t-test and Mann Whitney U test is used to data analyze. The results showed that companies with prospector strategies were more likely to carry out tax avoidance than defender. In addition, the activities of tax aggressiveness through investment in tax haven countries are mostly carried out by companies with a defender strategy.